Analisis Permintaan Tahu di Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Ovigeria Subroto Sinaga; Muhammad Badaruddin (Jurnal Ekonomi Islam, 2025)
Tofu is one of the most widely consumed foodstuffs in Indonesia. It is consumed by almost all levels of society. Tofu, made from agricultural products, namely soybeans, has been widely consumed by people since ancient times and its consumption is evenly distributed throughout Indonesia. The author is interested in examining how tofu consumption in Tenggarong sub-district, Kutai Kartanegara regency and wants to see the effect of tofu and tempeh prices as a comparison on tofu demand in Tenggarong sub-district. The results of the study indicate the influence of independent variables X1 and X2 in the regression equation Y = -50,178.37 + 20.48 X1 + 2,488.09 X2.